Effectiveness of Video Assisted Teaching On Knowledge Regarding Umbilical Cord Blood Collection for Stem Cell Therapy Among Women Attending an Antenatal Outpatient Clinic in A Selected Hospital in Puducherry, India - A Prospective Homogeneous Quasi-Experi: Life Sciences-Nursing - M, Annie Annal; R, Umamaheswari; S, Lavanya; V, Poongodi (International Journal of Life Science and Pharma Research, 2023)
Umbilical cord blood was previously considered a waste product. It is now used to treat a variety of diseases. Umbilical cord blood is the blood that remains after childbirth in the placenta and the attached umbilical cord. Cord blood is collected because stem cells found in it can be used to treat hematopoietic and genetic disorders. The study aimed to see how effective video-assisted teaching on cord blood collection for stem cell therapy was among antenatal women. A quasi-experimental (onegroup pretest and post-test) research design was adopted for this study. Sixty antenatal women who were attending antenatal OPD were selected by Purposive sampling. The structured questionnaire collected data to assess the level of knowledge regarding umbilical cord sample collection and stem cell therapy. In addition, structured, validated video-assisted teaching was done by experts in the field. The present study depicts that the pre-test means the level of knowledge of 5.48 with an SD of 2.04 was increased to 19.45 with an SD of 1.45 in the post-test after video-assisted teaching. Video-assisted teaching was found to be highly significant at p <0.001. The study concluded that the investigator-designed Video-assisted education effectively improved umbilical cord blood collection knowledge for stem cell therapy among antenatal women. The significant limitation of the study is that it is not double-blinded, as it involves a specific teaching course.